Unfair Masters and Rascally Servants? Labour Relations Among Bourgeois, Clerks and Voyageurs in the Montréal Fur Trade, 1780-1821 - Podruchny, Carolyn (Labour / Le Travail, 1999)
The Montreal fur trade labour system was organized around indentured servitude, patemalism, and cultural hegemony. French Canadian labourers signed legal contracts promising to obey their master in exchange for board and wages. These legal contracts were overshadowed by "social contracts" which signified continual negotiating for fair working conditions. Although voyageurs did not challenge the structure of the master and servant relationship, they continually pushed at the boundaries of their rights as workers. They diminished master authority through a "counter-theatre" of resistance, which inctuded working slowly, complaining, stealing provisions, and desetting the service.